AI and Blockchain Adoption in E-Government 3.0: A Systematic Review and Conceptual Framework - Nabil Abdallh Abbas Almotawkel; Abdulrahman Mohammed Hussein Obaid; Hamza Ali Abdul Rahman Qasem; Gameil Saad Hamzh Ali (Journal of Information System and Informatics, 2026)
This study presents a systematic review of the adoption of Artificial Intelligence (AI) and Blockchain technologies in E-Government 3.0 within developing countries, based on 99 reviewed studies published between 2020 and 2025. Using the PRISMA 2020 protocol, the review synthesizes existing literature to identify key barriers, opportunities, and emerging governance patterns. The findings suggest that while AI appears to enhance decision-making capabilities, and blockchain is associated with enhanced transparency and data integrity, their successful adoption appears to be constrained by institutional capacity, regulatory frameworks, organizational readiness, and digital trust. The results further indicate that technological factors alone are insufficient without alignment with governance structures and policy environments. Based on the synthesis, this study proposes the SIF-G3.0 conceptual framework, which integrates technological, institutional, regulatory, and trust dimensions as a conceptual model for understanding digital government transformation. The proposed SIF-G3.0 framework remains conceptual and has not yet been empirically validated. The evidence base included heterogeneous sources, including empirical, conceptual, bibliometric, and systematic review studies. The study also highlights critical research gaps and provides directions for future research in hybrid intelligent governance systems.